Bamboo raindrop drainage system - Yahaya, Maisarah; Kamaruzzaman, Aina Nazura; Johari, Nurul Athirah; Frans, Melsy; Wee, Hassnah (Universiti Teknologi MARA, Kedah, 2022)
Corrugated pipes are commonly used today, but clay and concrete are also used. Using drainage pipes constructed of various materials is common in the current market. This substance is prohibitively expensive, scarce, maintenance-intensive, and contaminates the water supplied by the plumbing element. In light of this scarcity, low-cost bamboo pipes are used as substitutes. In several regions of the world, bamboo is a renewable natural resource. Drainage is the natural elimination of a rainwater catchment's excess water to make it more acceptable for human usage. This study used bamboo with a predefined length and diameter as a rainwater drainage material in everyday activities, such as in the library and cleaning. The drainage system's role is to collect surface water or groundwater and direct it away, ensuring that the ballast bed is adequately drained. If appropriate conditions exist, the joint variability will be significant if the water table position is high, the rainfall has been hefty, and the site is sufficiently wet. Overall, bamboo as a material for rainwater drainage was determined to be successful. It can be used adequately as a substitute for various materials widespread on our market, providing cost savings, easy handling, and easy installation. In addition, unlike most other materials, bamboo pipes do not taint drinking water or react with the soil. This reduces the cost of purifying tap water for human use in specific industries. The new invention of the Bamboo Raindrop Drainage System would benefit communities and industries. It also aligned with the sustainable development goals initiated by the United Nations.